2021
DOI: 10.1029/2021gl092690
|View full text |Cite
|
Sign up to set email alerts
|

Cassini Observation of Relativistic Electron Butterfly Distributions in Saturn’s Inner Radiation Belts: Evidence for Acceleration by Local Processes

Abstract: The morphology of electron pitch angle distributions (PADs) helps to identify dynamic processes in Saturn's magnetosphere. Previous studies demonstrated convective transport being important for relativistic electron acceleration at L>4 in the inner magnetosphere, whereas closer to Saturn the situation is not as well established. We have investigated the PADs of relativistic electrons throughout radiation belts, using 13-year measurements from Cassini spacecraft. Our results show that at 3.5 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…In the present study, we will investigate if this transition also exists for >1 MeV electron PADs. A similar regime transition of electron PADs was observed by Cassini at Saturn, with electron PADs mostly field‐aligned or isotropic outward of M = 11 and pancake inward of this limit, but with butterfly distributions also present at M ∼ 8–11 and M ∼ 3 (Carbary et al., 2011; Clark et al., 2014; Yuan et al., 2021). Finally, Katoh et al.…”
Section: State Of the Art Of Energetic Electron Pads In The Jovian Ma...supporting
confidence: 63%
“…In the present study, we will investigate if this transition also exists for >1 MeV electron PADs. A similar regime transition of electron PADs was observed by Cassini at Saturn, with electron PADs mostly field‐aligned or isotropic outward of M = 11 and pancake inward of this limit, but with butterfly distributions also present at M ∼ 8–11 and M ∼ 3 (Carbary et al., 2011; Clark et al., 2014; Yuan et al., 2021). Finally, Katoh et al.…”
Section: State Of the Art Of Energetic Electron Pads In The Jovian Ma...supporting
confidence: 63%
“…This raises the question, if radial transport episodes are intense enough to occasionally fill the moon corridors (in the L-shell profiles of ultrarelativistic electrons like E7) at low latitudes, why do we not see that happening at high latitudes, during the proximal orbits? Yuan et al (2021) found that the same energetic electron measurements discussed here, including the 7-20 MeV ones measured by E7, have butterfly equatorial pitch angle distributions (PADs) outward of the main rings, peaking at an equatorial pitch angle around 55°, whereas proton PADs are peaked at 90°. They additionally showed that fluxes at equatorial pitch angles of ∼15°, i.e., the maximum value that could be measured at Cassiniʼs high-latitude proximal orbits in the L > 2.27 radiation belts, are more than 20 times below the peak values at ∼55°, indicating that the E7 signal falls rapidly with latitude at those distances.…”
Section: Grand Finale Orbitssupporting
confidence: 68%
“…At L‐shells close to the planet it has recently been demonstrated that butterfly PADs are observed inside of L = 3.5 at MeV energies (Yuan et al., 2021 ). This is in line with predictions from previous analysis of Z‐mode and chorus interactions with electrons (Woodfield et al., 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al. ( 2021 ) show that the electron MeV PADs just inside of the orbit of Enceladus (L = 3.9) are isotropic or pancake shaped but then rapidly become butterfly PADs inside of approximately 3.5 R S . This is the opposite behavior we would expect from both radial diffusion and rapid adiabatic transport further indicating the importance of the wave‐particle interactions inside of 3.5 R S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation